Racial Differences in Transportation Access to Employment in Chicago and Los Angeles, 1980 and 1990 - Chung, Chanjin; Myers, Samuel L; Saunders, Lisa (American Economic Review, 2001)
Racial Differences in Transportation Access to Employment in Chicago and Los Angeles, 1980 and 1990 by Chanjin Chung, Samuel L. Myers and Lisa Saunders. Published in volume 91, issue 2, pages 174-177 of American Economic Review, May 2001